2015
DOI: 10.1149/2.0101514jes
|View full text |Cite
|
Sign up to set email alerts
|

Review—High-Capacity Li[Ni1-xCox/2Mnx/2]O2(x= 0.1, 0.05, 0) Cathodes for Next-Generation Li-Ion Battery

Abstract: LiNiO 2 with theoretical capacity of 275 mAh g −1 is regarded as a promising cathode material for Li-ion batteries, but its potential capacity has not been fully realized due to the severe capacity loss in the first charge/discharge cycle. Via co-precipitation method, we synthesized Li[Ni 0.90 Co 0.05 Mn 0.05 ]O 2, Li[Ni 0.95 Co 0.025 Mn 0.025 ]O 2 , and LiNiO 2 which delivered 221, 230, and 240 mAh g −1 , respectively, when cycled from 2.7 to 4.3 V vs. Li 0 /Li + at 0.1 C and retained ∼70% of the initial capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 43 publications
2
76
0
Order By: Relevance
“…Meanwhile, the formation of rock‐salt phase usually accompanied by the oxygen loss which may induce capacity reduction, rapid voltage decay and lead to structure instability and thermal runaway [4d, 11a, 16] . However, some other reports suggested that the rock‐salt phase on the surface can be beneficial on the reversibility due to the pillaring effect [3c, 7, 22] . Here, we also investigated the evolution of TB close to the surface region during delithiation.…”
Section: Resultsmentioning
confidence: 94%
“…Meanwhile, the formation of rock‐salt phase usually accompanied by the oxygen loss which may induce capacity reduction, rapid voltage decay and lead to structure instability and thermal runaway [4d, 11a, 16] . However, some other reports suggested that the rock‐salt phase on the surface can be beneficial on the reversibility due to the pillaring effect [3c, 7, 22] . Here, we also investigated the evolution of TB close to the surface region during delithiation.…”
Section: Resultsmentioning
confidence: 94%
“…2,6,32 Raising the charge voltage limit to 4.7 V vs. Li + /Li results in increased utilization, 9 but lower capacity retention upon cycling due to rising cell impedance. 17,18 Figure S2 shows capacity retention data for half cells containing NMC-622 cycled to various voltage limits.…”
Section: Resultsmentioning
confidence: 99%
“…With a relatively high capacity and high operating voltage, nickel-rich layered transition metal oxides with a general formula of Li[Ni x Mn y Co 1ÀxÀy ]O 2 (x $ 0.5, Ni-rich NMCs) are considered most promising for high-energy LIBs in large-scale applications. [1][2][3][4][5][6] However, the poor high-voltage cycling stability of these oxide cathodes limits their commercial adoption. 7,8 Currently, there is an urgent need for fundamental understanding of the degradation mechanism and factors that control the degradation, especially at high voltages.…”
Section: Introductionmentioning
confidence: 99%